Clinical psychologists' perceptions of barriers and facilitators to engaging service users in index offence assessment and formulation within a medium secure unit. Issue 1 (2nd January 2018) - Rusbridge, Sarah; Tooze, Oliver; Griffith, Emma; Wilkinson-Tough, Megan
Abstract: Index offence assessment and formulation (IOAF) helps service users (SU) in secure units to make sense of their index offence, provides detailed understanding of risk and contributes to treatment planning and discharge decisions. Clinical psychologists' perceptions of barriers and facilitators to engaging SUs in IOAF within the men's and women's services of one medium secure unit were explored through focus groups. Thematic analysis identified two relevant domains: person-specific factors and the organisational context. Person-specific barriers included challenges in working with fragmented narratives, conflicting motivations to engage, SU defences and distorted perceptions of clinical psychologists' roles. Giving clarity and choice to SUs facilitated engagement with the work. Regarding the organisational context, clinical psychologists within both services identified the importance of having adequate resources and care-team support to complete this work. Findings highlight the importance of developing an evidence-based framework for IOAF to be embedded within clear 'risk' care pathways through secure services.